2015
DOI: 10.1080/15476286.2015.1071011
|View full text |Cite
|
Sign up to set email alerts
|

The multicopy sRNA LhrC controls expression of the oligopeptide-binding protein OppA inListeria monocytogenes

Abstract: Listeria monocytogenes is the causative agent of the foodborne disease listeriosis. During infection, L. monocytogenes produces an array of non-coding RNAs, including the multicopy sRNA LhrC. These five, nearly identical sRNAs are highly induced in response to cell envelope stress and target the virulence adhesin lapB at the post-transcriptional level. Here, we demonstrate that LhrC controls expression of additional genes encoding cell envelope-associated proteins with virulence function. Using transcriptomics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 56 publications
2
69
0
Order By: Relevance
“…3C]) and the subtilisin-like protease (SCLAV_p0750), which were expressed at some sampling times at levels 10.1-and 6.4-fold higher than those in the wild-type strain, respectively (Table 1). Coregulated expression of independent substrate-binding proteins and secreted proteins has been described previously (23).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3C]) and the subtilisin-like protease (SCLAV_p0750), which were expressed at some sampling times at levels 10.1-and 6.4-fold higher than those in the wild-type strain, respectively (Table 1). Coregulated expression of independent substrate-binding proteins and secreted proteins has been described previously (23).…”
Section: Resultsmentioning
confidence: 99%
“…OppA periplasmic proteins are important in chemotaxis and virulence due to their substrate-binding and transport abilities as part of ABC systems (23,28). In addition, ecto-ATPase activity (29) or chaperone-like functions in protein folding (30) have been described for these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies in L. monocytogenes showed that the Hfqbinding sRNA LhrC also acts by direct base pairing to the RBS of partner mRNAs, but no role for Hfq has been found so far in controlling the stability or regulatory activities of LhrC [8,[11][12][13]. LhrC is a multicopy sRNA and the LhrC family comprises seven siblings: LhrC1-5, Rli22 and Rli33-1 (reviewed in [5]).…”
Section: Introductionmentioning
confidence: 99%
“…For LhrC1-5 and Rli22, induction relies on the twocomponent system LisRK, whereas the general stress sigma factor SigmaB controls expression of Rli33-1 [11,13]. The LhrC family of sRNAs has been shown to target mRNAs encoding surfaceexposed virulence-associated proteins, including the virulence adhesin LapB, the oligo-peptide binding protein OppA, and the CD4 + T cell-stimulating antigen TcsA [11,12]. In all three cases, the sRNAs exert a negative effect on translation, and for lapB and oppA, the LhrCs are known to act by direct base pairing to the RBS, leading to inhibition of translation followed by mRNA degradation [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation